Tradition Music of Bas as Entertainment Media and Strengthening Reflection of National Character Values - Muh. Arqam (Universitas Muhammadiyah Enrekang, 2025)
This study aimed to describe extent of role of bamboo musical performance (Bas) in celebration of the 72nd anniversary of the Independence Day of the Republic of Indonesia in Baraka District Enrekang Regency and describe crystallization of character values contained in the tradition musical performance of Bas. This study was qualitative. The source of data was from the results of observation, interviews and documentation. Data analysis was done by data reduction, data presentation, and verification or conclusion. The result showed that the roles of bamboo musical performance in the anniversary of the Republic of Indonesia in Baraka District were; (1) as the entertainment media; and (2) the character value contained religious, nationalist, independent, mutual cooperation (gotong royong) and integrity. So that, tradition music of Bas can instill cultural awareness to Massenrempulu society in general, especially practitioners and art educators in Enrekang Regency.